2018
DOI: 10.1016/j.jeconbus.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Institutions: Key variable for economic development in Latin America

Abstract: This article examines economic development from 1996 to 2015 for 192 countries and specifically Latin America. Evidence shows that each 0.1-point increase in institutions impacts a 3.9% improvement in Latin American per capita output versus a 2.6% effect on world development. This new evidence from Latin America shows a missing opportunity to develop at higher annual pace than the 2.14% average, mainly due to the deterioration in rule of law. We conjecture the efficiency of monetary/fiscal policies will improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…In recent years there are many domestic and foreign scientific studies in this field. Nakabashi et al (2013), Alexiou et al (2014), Acemoglu et al (2014), Vianna and Mollick (2018), Salman et al (2019), Ha (2016), Ngo and Nguyen (2020) concluded that institutions have positive impacts on economic growth. However, Dias and Tebaldi (2012) and Acemoglu et al (2015) did not find a relationship between institutions and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there are many domestic and foreign scientific studies in this field. Nakabashi et al (2013), Alexiou et al (2014), Acemoglu et al (2014), Vianna and Mollick (2018), Salman et al (2019), Ha (2016), Ngo and Nguyen (2020) concluded that institutions have positive impacts on economic growth. However, Dias and Tebaldi (2012) and Acemoglu et al (2015) did not find a relationship between institutions and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…the results show that venture capital can improve economic growth. Vianna and Mollick, (2018) article examines economic development from 1996 to 2015 for 192 countries and specifically Latin America. The result shows that that each 0.1-point increase in institutions impacts a 3.9% improvement in Latin American per capita output versus a 2.6% effect on world development.…”
Section: Introductionmentioning
confidence: 99%
“…These are all institutional inefficiencies slowing down economic growth especially in Africa. It is pertinent for policymakers to initiate actions acknowledging the positive link between strong institutions and economic progress (Vianna & Mollick, 2018).…”
Section: Food Waste Situation In Africa and Around The Worldmentioning
confidence: 99%
“…Feed safety is guided by several control measures, including certification, registration, strict feed standards coupled with treatment technologies. This introduction and implementation of regulations and laws have not experienced disease outbreaks associated with food waste-derived feeds (Vianna & Mollick, 2018).…”
Section: South Koreamentioning
confidence: 99%